2007
DOI: 10.4161/cc.6.18.4706
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Cyclins Determined by Electrostatics

Abstract: ACKnowLeDGementSBII and IMCB are A-STAR institutes funded by BMRC. We thank Michael Schaefer for providing us with unpublished parameters for version 3 of the analytical continuum solvent method. AbStrACtCyclin dependent kinases (CDK) associate with cyclins to regulate cell cycle progression and gene transcription by phosphorylating key proteins. The different cyclin-CDK complexes display differences in substrate specificities with substrates binding across a shallow, hydrophobic and substrate-binding pocket k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Although additional domains may be involved, these differences between CYB-1 and CYB-3 probably affect substrate specificity, as they concern the only substrate-docking site in cyclins known to date. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Although additional domains may be involved, these differences between CYB-1 and CYB-3 probably affect substrate specificity, as they concern the only substrate-docking site in cyclins known to date. 47 …”
Section: Discussionmentioning
confidence: 99%
“…the function of regulating the cyclin-Cdk kinase activity and inducing G 2 /M arrest. 24,25 We showed that overexpression of CCDC154 significantly reduced cyclin B1 and induced G 2 /M cell cycle arrest. These results, consistent with previous reports, imply that the cyclin-binding motifs play a critical role in cell growth regulation.…”
Section: Discussionmentioning
confidence: 96%
“…These proinflammatory roles of cyclin-CDK signaling occur through the control of gene expression (15)(16)(17), suggesting that this is largely independent from their role in cell cycle regulation in macrophages and neutrophils. Because CDK functions largely depend on their cyclin partner for substrate recognition (21,22), it is therefore reasonable to hypothesize that cyclins serve as de facto regulators of CDK activity in immune responses.…”
Section: Introductionmentioning
confidence: 99%